Adipose-Derived Mesenchymal Stem Cells for the Treatment of Articular Cartilage: A Systematic Review on Preclinical and Clinical Evidence - Francesco Perdisa; Natalia Gostyńska; Alice Roffi; Giuseppe Filardo; Maurilio Marcacci; Elizaveta Kon (Stem Cells International)
Among the current therapeutic approaches for the regeneration of damaged articular cartilage, none has yet proven to offer results comparable to those of native hyaline cartilage. Recently, it has been claimed that the use of mesenchymal stem cells (MSCs) provides greater regenerative potential than differentiated cells, such as chondrocytes. Among the different kinds of MSCs available, adipose-derived mesenchymal stem cells (ADSCs) are emerging due to their abundancy and easiness to harvest. However, their mechanism of action and potential for cartilage regeneration are still under investigation, and many other aspects still need to be clarified. The aim of this systematic review is to give an overview of in vivo studies dealing with ADSCs, by summarizing the main evidence for the treatment of cartilage disease of the knee.